Review of the genus Blosyrus Schoenherr (Coleoptera: Curculionidae: Entiminae) from India and adjacent countries. (3rd July 2018) - Mahendiran, Govindasamy; Gnaneswaran, Rajendramani; Ramamurthy, Vilayanoor Venkataraman
Abstract: Nine species of the genus Blosyrus (Schoenherr, 1826) (Curculionidae: Entiminae) occurring in India, Sri Lanka and Myanmar are revised. The earlier known seven species are redescribed, while two new species Blosyrus marshalli sp. nov. and Blosyrus thompsoni sp. nov., are described. The subspecies spongifer upgraded to species status upon phenotypic variations, is supported by its geographical distribution. The genus description is updated and a key to the species provided.